The Correlation Between Knowledge Level And Parents Skills In Providing First Aid For Burn Injuries In Toddlers - Kiki Sri Rahmandani; Mustiah Yulistiani; Endiyono; Atika Dhiah Anggraeni (Institut Citra Internasional, 2026)
Burns are a common type of injury in the home, especially in children. Proper first aid is crucial to prevent further complications. Parents, as primary caregivers, play a crucial role in providing first aid for burns. The level of knowledge parents possess is crucial in relation to their skills in administering first aid appropriately. This study aimed to determine the relationship between the level of knowledge and the skills of parents in administering first aid for burns in Cindaga Village. This study used a quantitative research design with a cross-sectional approach. The sampling technique used was purposive sampling of 70 respondents. Data were collected using questionnaires and observation sheets/checklists. Data analysis was performed using the Chi Square statistical test. The results showed that the majority of respondents had a good level of knowledge (25 respondents (35.7%), and skills in the fairly skilled category (26 respondents (34.3%). This indicates a significant relationship between the level of knowledge and the skills of parents in administering first aid for burns with a p-value of 0.01 (<0.05). The conclusion of this study is that there is a significant relationship between parental knowledge and skills in first aid for burns in toddlers in Cindaga Village. Therefore, efforts are needed to improve health education for the community.